Pyrolysis kinetics-dependent suitability of Al-based MOFs (CAU-10) for controlling amorphous γ-Al2O3 generation - Donald Raoul Tchuifon Tchuifon; Lucresse Kora Tioma Nguena; Giscard Doungmo; Sandrale Grace Mokue Mafo; Frank Dorinel Solefack Feudjio; Cyrille Ghislain Fotsop (Chemical Thermodynamics and Thermal Analysis)
The thermal degradation of Al-based MOF (CAU-10) were analyzed based on an isoconversional calculation method. The ɤ-Al2O3 formation were characterized using XRD, FTIR, 27Al NMR-MAS and SEM/EDX. The apparent activation energy Ea was evaluated using the iterative isoconversional method. The values of these energies related to the first step (deshydration) and the second step (framework destruction) for the thermal decomposition of CAU-10 reached 35 and 217 kJ/mol, respectively. This indicates that the second step is a complex kinetic process. In addition, the kinetic processes occur in a single step and can be characterized by a unique kinetic triplet (Ea, A, g(α)). For both decomposition steps of CAU-10, the mechanism includes chemical reactions, nucleation, branched nuclei, and three-dimensional diffusion in the first and second phases. According to the Kissinger-Akahira-Sunose (KAS) and Flynn-Wall-Ozawa (FWO) models in the first step, the Gibbs free energy is between 91.099 kJ/mol and 97.824 kJ/mol; between 242.651 kJ/mol and 244.285 kJ/mol, respectively. This analysis based on thermal measurements combined with structural measurements has highlighted the energetic potential of MOFs synthesis from aluminum exposed to a vapor explosion in a basic context.